Leo Copers : Zonder titel. - Paleis voor Schone Kunsten, Brussel (Gent : Imschoot Uitgevers, 1991)
Van den Abeele, Albijn ; van den Berghe, Frits ; Brusselmans, Jean ; Copers, Leo ; Degouve de Nuncques, William ; Ensor, James ; Frederic, Léon ; Khnopff, Fernand ; Mellery, Xavier ; Minne, George ; Rouault, Georges ; Van Rysselberghe, Théodore ; De Smet, Gustave ; De Smet, Léon ; Smits, Jacob ; Spilliaert, Léon ; Tytgat, Edgard ; de Woestyne, Gustave Van ; Wouters, Rik
Linnen band met stofomslag. Pp: 80. Chocolate cover, full colour printing, with brown ink on one side. A friend of alchemy and the transformative power of images, Copers uses brown curtain-like pages left uncut, to hide a catalogue of treasures from the art museum in Ghent.
Nederlands
Antichambres - Affinités sélectives VIII, Paleis voor Schone Kunsten, Brussel, 22.02.1991 - 24.03.1991
kunstcatalogus